Observation of pedestal mode spreading into SOL and broadening of divertor particle flux width on EAST tokamak - T. Zhang; F.F. Long; G.S. Li; X.Q. Xu; J.B. Liu; K.N. Geng; Y.F. Wang; B. Zhang; K.X. Ye; Z.Q. Zhou; F.B. Zhong; F. Wen; et al. (Nuclear Fusion)
Pedestal turbulence spreading into a crape-off layer (SOL) can be used to explain the experimentally observed strong pedestal-SOL coupling and is expected to be important for the broadening of divertor deposition profiles in future devices (Xu et al 2019 Nucl. Fusion 59 126039). In the EAST tokamak, it is found that an electromagnetic (EM) mode in the pedestal region can spread into the SOL and broaden the divertor particle flux width. Multi-channel fluctuation reflectometry is used to measure the density fluctuations at the plasma edge. The EM mode rotates in the electron diamagnetic drift direction in the lab frame with a frequency range of [40–90] kHz, toroidal mode number n = 12–13 and poloidal wavenumber k _θ = 0.41 cm ^−1 . The mode amplitude peaks around the maximum of the pedestal density gradient. As the mode amplitude increases, the reflectometry channel in the SOL can clearly capture the mode. This result suggests that the EM mode is excited in the pedestal gradient region and spreads into the SOL. It is further found that the particle flux deposition profile in the divertor is broadened as the EM mode appears.